Fabrication of Lithographically Defined Chemically Patterned Polymer Brushes and Mats - Liu, Chi-Chun; Han, Eungnak; Onses, M. Serdar; Thode, Christopher J; Ji, Shengxiang; Gopalan, Padma; Nealey, Paul F (Macromolecules, 2011)
Chemically patterned surfaces comprised of polymer mats and brushes of well-defined chemistry were fabricated at the length scale of 10 nm. A key concept is the integration of new materials, cross-linked polymer mats, with traditional lithographic processing. Resist was patterned on top of cross-linked polystyrene mats. After etching, regions of the remaining mat with dimensions ranging from 10 to 35 nm were separated by interspatial openings to the underlying substrate. End-grafted polymer brushes, in this case hydroxyl-terminated poly(2-vinylpyridine) or polystyrene−poly(methyl methacrylate) random copolymer, were grafted into the exposed, interspatial regions from films spin-coated over the patterned mat. Both block copolymer wetting studies, with polystyrene-block-poly(methyl methacrylate) (PS-b-PMMA), and near-edge X-ray fine structure spectroscopy showed that with sufficient cross-linking the polymer mat chemistry was unaffected by the subsequent grafting of the polymer brush. The precise definition of both the chemistry and the geometry was demostrated with two sensitive applications of nanoscale chemical patterns: the site-specific immobilization of Au nanoparticles and the directed assembly of overlying PS-b-PMMA films.